Antioxidants activity and physicochemical properties of honey from social bees of the Brazilian semiarid region - Silva, Irana Paim (2018)
This study compared the nutraceutical potential of Apis mellifera and Melipona quadrifasciata anthidioides honeys from the semiarid region of Bahia, Brazil, using microbiological, melissopalynological, and physicochemical techniques. Total phenols and flavonoids and the antioxidant activity were also determined. All samples had good microbiological quality and safety with an absence of coliforms, Escherichia coli, Salmonella spp., Staphylococcus coagulase positive and Clostridium sulphite reducing spores. Were identified 41 pollen types belonging to 23 botanical families. Myrtaceae, Anacardiaceae, and Sapindaceae were the predominant pollen types in A. mellifera honey, while honey Malvaceae was the most representative in the M. q. anthidioides. Regarding the physicochemical parameters evaluated, 75% complied with the standards established by the Brazilian and European quality legislation. The honey samples of A. mellifera had higher values of phenolic compounds and flavonoids (260.0 to 341.51 mgGAE.kg−1 and from 114.44 to 216.29 mgQE.kg−1, respectively). The samples from M. q. anthidioides presented higher antioxidant activity. The honeys of A. mellifera and M. q. anthidioides from the semiarid regions presented distinct botanical compositions, suggesting that both species use different plant sources, which possibly influenced the parameters related to honey quality as well as the content of phenolic compounds.